Genotyping and Phylogenetic Analysis of Group B Streptococcus by Multiple Locus Variable Number Tandem Repeat Analysis in Iran: - Aghazadeh, Mohammad; Khodaei, Farzaneh; Sadeghi Kalani, Behrooz; Alizadeh, Naser; Hassani, Alka; Najafi, Mohammad; Kalantar, Enayatollah; Amini, Abbas (Galen Medical Journal, 2018)
Background: Group B streptococcus (GBS), also known as Streptococcus agalactiae, is well known as a causative agent for neonatal invasive diseases; it is also a major pathogen in adults. Analytic epidemiology is required to monitor the clinical isolates of GBS. However, there is insufficient information on the genetic background of GBS in Iran, and this information is needed to guide and develop a GBS vaccine. Materials and Methods: In total, 90 well-characterized GBS isolates were collected from April 2014 to August 2015. In this study, molecular typing was used to disclose a relationship between the multiple-locus variable number tandem repeat analysis (MLVA) types, serotyping, and pilus islands. The isolates were characterized by the types of capsular polysaccharides and pilus islands and were examined by MLVA to study the epidemiological relationship of isolates. Results: The results indicate that there is a significant relationship between the distribution of serotypes and pilus island genes; GBS isolates were differentiated into 12 types by capsular polysaccharides and pilus islands analysis. The discriminatory power of an MLVA analysis was high based on the five most variable numbers of tandem repeat loci and 44 MLVA types that were identified. Conclusions: This study has provided useful insights into the genetic heterogeneity of GBS isolates in Tehran and Alborz, Iran. The extensive distribution of pilus islands in various serotypes and MLVA types throughout the GBS population refers to the advancement of the pilus-based GBS vaccines. [GMJ.2018;7:e1121]